ESTIMACIONES DEL IMPACTO DEL LÍMITE DE CRECIMIENTO (ANILLO DE CONTENCIÓN) SOBRE LOS VALORES DEL SUELO EN EL NORTE DE HEREDIA, 1997-2007 - Pujol M., Rosendo (2022)
This paper seeks to quantify the causal impact of the growth boundary in northern Heredia. Using the gradient of prices and a model of difference-in-differences, we estimatedthe differential in land value attributable to the impact of the regulation on the growthlimit for the 1997-2007 periods. This effect is manifested by a change in the slope of theprice gradient, indicating that the highest and the best use in the absence of regulation hasbeen restricted - which means that the regulation has been successful in reducing the levelof urban development in the protection zone.